Association of Interleukin-6 Signaling and C-Reactive Protein With Intracranial Aneurysm: A Mendelian Randomization and Genetic Correlation Study - Niu, Peng-Peng; Wang, Xue; Xu, Yu-Ming (Frontiers in Genetics, 2021)
Background and objective: Evidence suggested that interleukin-6 (IL6) signaling was causally associated with aortic aneurysm independently of the effect of C-reactive protein (CRP). We aimed to explore the genetic overlap and associations between inflammation (IL6 signaling and CRP) and intracranial aneurysm (IA) risk. Methods: Two-sample Mendelian randomization (MR) method was used to assess the causal effects of soluble IL6 receptor (sIL6R) (n=21,758) and CRP (n=204,402) levels on IA (7,495 cases and 71,934 controls) risk using genome-wide association study summary data of European individuals. Cross-trait linkage disequilibrium score regression was used to estimate the genetic correlations of CRP (n=400,094) with IA. Results: MR analyses showed that circulating sIL6R and CRP levels were not associated with the risk of IA. The odds ratios based on the inverse variance-weighted method were 0.986 (0.950–1.023, p = 0.45) and 0.957 (0.846–1.084, p = 0.49) for sIL6R and CRP, respectively. MR analyses using data of ruptured and unruptured IA each showed no association. Linkage disequilibrium score regression showed that the genetic correlation between CRP and IA was 0.16 (se = 0.04, p = 0.0003). The genetic correlation diminished after conditioning IA on blood pressure (0.07±0.05, p = 0.16), smoking (0.02±0.05, p = 0.65), or blood pressure plus smoking (–0.03±0.05, p = 0.53). Conclusions: Using associated genetic variants as instrument variables, two-sample MR analyses showed no evidence that circulating sIL6R and CRP levels were associated with IA risk. Although a positive genetic correlation was found between CRP levels and IA risk, it was mainly driven by the shared genetic background of blood pressure and smoking with both CRP and IA.